T31. WHY IS CONTOUR INTEGRATION IMPAIRED IN SCHIZOPHRENIA? NEW INSIGHTS FROM A CROSS-DIAGNOSTIC PARAMETRICALLY VARYING BEHAVIORAL TASK. (9th April 2019) - Crespo, Laura; Barch, Deanna; Cole, Michael; Krekelberg, Bart; Silverstein, Steven; Smith, Dillon; Coughlin, Brendon; Keane, Brian
Abstract: Background: Schizophrenia patients (SZ) poorly integrate multiple spatially segregated oriented elements into cohesive contours and shapes, and this impairment becomes more pronounced as the stimulus is globally scaled down in size (d=1.7; Keane et al., 2016, J Abnorm Psychol). But what stimulus properties drive this scaling effect and how specific is it to the schizophrenia phenotype? Addressing this issue will yield important clues for building behavioral tasks that flag current or impending psychosis; it will also clarify the visual mechanisms disturbed. Methods: We compared SZ patients (N=5), bipolar disorder patients (BDs; N=9), and well-matched healthy controls (N=7) on a psychophysical task in which subjects sought to identify the screen quadrant location of an integrated circular target. Each target was rendered visible by eight co-circular edge elements distributed along its circumference. Task difficulty was staircase controlled and depended on the number of noise elements co-presented with the target. Noise and target elements were drawn as Gabors, which are sinusoidal luminance gratings multiplied by a circularly symmetric Gaussian filter. There were 16 different stimulus conditions corresponding to the crossings of four different stimulus parameters that would change with spatial scaling: (1) Gabor spatial frequency (6 or 12 cycles/deg), (2) Gabor width (Gaussian envelope SD of 2.4 or 4.8 arcmin), (3) target eccentricity (2.3 or 4.7 degrees from central fixation), and (4) target radius (.74 or 1.5 deg). Results: As expected, targets were easier to detect when closer to fixation and having a smaller radius (resulting in smaller inter-element distance) (ps<.05), and when individual elements had a lower spatial frequency and larger width (ps<.05). None of these main effects depended on subject group (p>.08). Five of the six two-way-interactions were significant (exception: eccentricity by Gabor width) but none depended on subject group (p>.28). Subject group interacted with spatial frequency, eccentricity, and Gabor width (four-way interaction, p<.01); it also interacted with eccentricity, radius, and spatial frequency (four-way interaction, p<.05). Comparing controls and BDs, there was no group differences or interactions (ps>.05). Comparing controls to SZs, there was the same pair of four-way interactions just described (ps<.01). Comparing SZs to BDs, there was a four-way interaction as before with spatial frequency, eccentricity, and Gabor width (p=.04). To state this last result in another way, among bipolar patients and controls, increasing the Gabor width improved contour integration performance more for low than for high spatial frequency stimuli, and this effect was more apparent for high eccentricity displays (p<.001). Among SZs, increasing eccentricity did not accentuate the two-way interaction and appeared to have the opposite effect (p>.2). Thus, SZ may involve more uncertainty at locations closer to fixation such that broadening the window of the Gabor (to reveal more of the waveform) offers more benefit to those subjects at those same locations. Discussion: These results, while still very preliminary, suggest that contour integration deficits worsen in SZ when the spatial scaling factors jointly vary, viz., when the eccentricity is reduced, the Gabor width is reduced, the spatial frequency is increased, and the target radius is minimized. In a word, it appears that potentially all aspects of spatial scaling may contribute to contour integration deficits in schizophrenia perhaps because of inadequate sampling within parafoveal relative to peripheral retinotopic locations; these deficits appear to be fairly specific to schizophrenia.